2018
DOI: 10.1590/abd1806-4841.20187162
|View full text |Cite
|
Sign up to set email alerts
|

Diphencyprone as a therapeutic option in cutaneous metastasis of melanoma. A single-institution experience

Abstract: Diphencyprone has been reported as a local immunotherapy for cutaneous melanoma metastases. We aim to report cases of melanoma patients treated with diphencyprone in a single Brazilian institution and highlight their outcomes. Since 2012, we have treated 16 melanoma patients with cutaneous metastases with topical diphencyprone. To date, we have had 37.5% of complete response, 25% of partial responses, and 31.25% patients without any response. Treatment was well tolerated and local toxicity was easily controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The response to DPCP and the survival rates are in keeping with the results published by the current group, 7 two Australian cohorts, 5,6 and two smaller Canadian and Brazilian cohorts. 24,25 Collation of the published data for 192 patients to date shows that DPCP has an overall response (CR ? PR) rate of 64.6%.…”
Section: Discussionmentioning
confidence: 99%
“…The response to DPCP and the survival rates are in keeping with the results published by the current group, 7 two Australian cohorts, 5,6 and two smaller Canadian and Brazilian cohorts. 24,25 Collation of the published data for 192 patients to date shows that DPCP has an overall response (CR ? PR) rate of 64.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Gibbons et al, reported data on 16 patients with CMMs treated with topical diphencyprone, describing a 37.5% complete response and a 25% partial response. The treatment was well tolerated [133]. Among 50 patients with CMMs, Damian et al, reported a complete clearance of cutaneous disease in 46% and a partial response in 38% of patients, assessing that diphencyprone should be considered for patients with skin metastases refractory to other therapies [134].…”
Section: Diphencypronementioning
confidence: 97%
“…A Brazilian study showed that diphencyprone can lead to up to 37% of complete response in cases of cutaneous melanoma metastases. 62 …”
Section: Treatmentmentioning
confidence: 99%